The language way of expression of city space in M. Semenko’s poetry (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The article deals with the the structure of art space in connection with lexical and semantic ways of expression of realistic city space. The questions on traditions and innovation, dynamic of development of a language image of the world at the poet are examined.
Keywords: space; language image of space; space of city